LINGUISTIC AND CULTURAL CHARACTERISTICS OF METAPHORS IN THE LANGUAGE OF TURKISH SOURCES - Abdunazarovna , Abdujabbarova Feruza (PT. Antis International Publisher, 2024)
In the article, the linguistic and cultural characteristics of metaphors in the language of Turkish sources are covered based on the work